AlxCoCrFeNi high entropy alloys with superior hot corrosion resistance to Na2SO4 + 25% NaCl at 900 °C. (15th July 2021) - Li, Ling; Lu, Jie; Liu, Xuanzhen; Dong, Tao; Zhao, Xiaofeng; Yang, Fan; Guo, Fangwei
Graphical abstract: Highlights: The high-entropy alloys show shallow internal corrosion attack. Coherent phase interfaces reduce short-circuit diffusion paths. The infiltration of corrosion components through phase interfaces leading to severe internal attacks in NiCoCrAl. The high-entropy alloys have a more effective Al supply to resist hot corrosion. Uniform distribution and sufficient supply of Al and Cr result in a uniform shallow attack. Abstract: Hot corrosion behaviors of Y, Hf-codoped Al x CoCrFeNi (Al x, x = 0.7, 1.0, and 1.3) high-entropy alloys (HEAs) under Na2 SO4 + 25 % NaCl molten salts at 900 °C were investigated and compared with those of the conventional NiCoCrAl alloy. The results show Al1.0 and Al1.3 with spinodally decomposed structure of A2 + B2 phases possess significantly enhanced hot corrosion resistance than Al0.7 with eutectic lamellar structure and NiCoCrAl. The superior hot corrosion resistance is attributed to the loop-locked coherent phase interfaces in the modulated structure, along with the improved availability of Al and the high Cr content.